A Heuristic Model for Planning of Single Wire Earth Return Power Distribution Systems - Bakkabulindi, Geofrey; Hesamzadeh2, Mohammad R.; Amelin, Mikael; Silva, Izael P. Da; Lugujjo, Eriabu (Bakkabulindi, G., Hesamzadeh, M. R., Amelin, M., Da Silva, I. P., & Lugujjo, E. (2011)., 2011)
The planning of distribution networks with earth return is highly dependent on the ground’s electrical properties. This study incorporates a load flow algorithm for Single Wire Earth Return (SWER) networks into the planning of such systems. The earth’s variable conductive properties are modelled into the load flow algorithm and the model considers load growth over different time periods. It includes optimal conductor selection for the SWER system and can also be used to forecast when an initially selected conductor will need to be upgraded. The planning procedure is based on indices derived through an iterative heuristic process that aims to minimise losses and investment costs subject to load flow constraints. A case study in Uganda is used to test the model’s practical application.
Keywords: Power distribution planning, Power flow analysis, Single Wire Earth Return, Rural electrification